2000 Distinguished Service Award: R. Gary Rozier, DDS, MPH - B. Alex White, DDS, DrPH (Blackwell Synergy, 2001)
The Distinguished Service Award is presented annually to an individual for excellent and distinguished service to public health dentistry. It is the highest honor that the American Association of Public Health Dentistry can bestow. This year’s recipient is Dr. Gary Rozier. Gary has had a very distinguished career and has committed himself to improving the public’s oral health through research and teachmg.